2022
DOI: 10.1186/s40364-022-00438-5
|View full text |Cite
|
Sign up to set email alerts
|

Protein biomarkers in cervicovaginal lavages for detection of endometrial cancer

Abstract: Background Rates of endometrial cancer (EC) are increasing. For a definitive diagnosis, women undergo various time-consuming and painful medical procedures, such as endometrial biopsy with or without hysteroscopy, and dilation and curettage, which may create a barrier to early detection and treatment, particularly for women with inadequate healthcare access. Thus, there is a need to develop robust EC diagnostics based on non- or minimally-invasive sampling. The objective of this study was to qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…The results of this study suggest that changes in D-D and Fib levels could be used to predict EC. CA199 was also included in this study and our results confirmed its application in predicting EC, which is consistent with previous study ( 37 ).…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study suggest that changes in D-D and Fib levels could be used to predict EC. CA199 was also included in this study and our results confirmed its application in predicting EC, which is consistent with previous study ( 37 ).…”
Section: Discussionsupporting
confidence: 91%
“…In some analyses, endometrial cancer is grouped as “endometrial cancer-All” ( n = 63) and includes both grade 1/2 EEC and other endometrial cancer. Clinical and demographic information for this cohort was previously described ( 22 ). Key demographic information is displayed in Table 1 and additional information relating to participant demographics and characteristics are included in Supplementary Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…CVL samples were utilized for immunoproteome analysis as previously described [ 50 ]. Briefly, levels of 41 proteins were measured in CVL samples using the Milliplex MAP Magnetic Bead Immunoassays: Human Cytokine Chemokine Panel 1 (Millipore, Billerica, MA) following the manufacturer’s protocols [ 50 ]. Data was collected using a Bio-Plex 200 instrument and analyzed using Manager 5.0 software (Bio-Rad, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%